(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Traffic controllers work in the middle of innumerous noisy and polluting vehicles and endure physical strain in an environment polluted by fumes, exhaust of vehicles, use of blowing horns, blow of dust in the air, etc. Their stressful lives often make them resort to unhealthy food choices, ill-timed and unbalanced meals, leading to many problems. Objective: The present study aimed to analyse the nutritional status of personnel controlling traffic in a tertiary care hospital of Delhi through the ‘ABCD’ approach of nutritional assessment: Anthropometric, Biochemical, Clinical and Dietary status to get a fair idea about their individual nutritional needs. Methodology: It was a prospective analysis done in hospital of Delhi by assessing anthropometry, biochemical, clinical parameters, and dietary status on a sample size of 48 personnel controlling traffic. Results: The results of the study showed that only few of the subjects were of appropriate weight (29%), were consuming adequate calories (18.75%), and were consuming adequate proteins (16.66%). Majority of them had health problems with deranged blood parameters and many were also subjected to substance abuse and had very little and inaccurate nutritional knowledge. Conclusion: The study highlighted the need for proper nutrition education sessions for them and the importance of nutritional counseling amongst them. Better health outcomes can thus be hoped with this prospective study in the target population.